2020
DOI: 10.3390/agronomy10030381
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Release Fertilizer Improves the Growth, Quality, and Nutrient Utilization of Wintering Chinese Chives (Allium tuberosum Rottler ex Spreng.)

Abstract: Excessive application of fertilizers leads to the loss of a high amount of nutrients and low fertilizer utilization, which severely restricts crop productivity. Establishing better fertilizer usage practices can mitigate the adverse effects of excessive fertilizer use in agricultural practices. This study determined the effects of slow-release fertilizers on the growth; quality; root and nitrate reductase activity; accumulation; distribution of nitrogen (N), phosphorus (P), and potassium (K) in roots, stems, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
(30 reference statements)
3
33
0
Order By: Relevance
“…Nitrogen is a major structural component of protein, and N addition could result in increasing protein content or improving seed quality 41 . Properly managing N application is essential in N transformation and remobilization between vegetative and economic organs in plants over the grain filling process, which is beneficial for obtaining good appearance and seed quality 22 . The CR urea significantly enhanced seed quality and improved the appearance and taste quality, which is beneficial for performance in the agricultural market 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen is a major structural component of protein, and N addition could result in increasing protein content or improving seed quality 41 . Properly managing N application is essential in N transformation and remobilization between vegetative and economic organs in plants over the grain filling process, which is beneficial for obtaining good appearance and seed quality 22 . The CR urea significantly enhanced seed quality and improved the appearance and taste quality, which is beneficial for performance in the agricultural market 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, proper N fertilizer application is essential in improving grain quality because of an increase of N uptake and its remobilization to economic organ over the reproductive stage, thus increasing seed yield and economic benefits 19,20 . However, previous studies have shown that conventional N management practices producing increased seed yield tend to achieve lower grain quality and decrease soil fertility 21,22 . In recent years, focus has shifted towards considering the relationship with seed quality and soil fertility while maintaining high seed yield and economic benefits delivered by properly management N application.…”
Section: Introductionmentioning
confidence: 99%
“…Although not formally considered an essential plant nutrient, Gad et al [26] demonstrated that application of Co, especially in combination with animal wastes, increased Moringa oleifera Lam growth, yield, and plant Co in plants grown in semi-arid soils. Wang et al [27] showed that applying slow-release fertilizer resulted in reduced NPK rates being needed for optimum production, while increasing yield and net return for fertilization of chives. Aslam et al [28] demonstrated increased wheat yield and yield components with application of NPK + vermicompost compared to NPK alone.…”
Section: Nutrient Sourcesmentioning
confidence: 99%
“…Meanwhile, the NO 3 − dosage can influence growing substrate pH, especially in nutrient recirculating systems 18 . It has been found that an increase of NO 3 − dosage caused a significant increase of medicinal and phytochemical compounds of E. purpurea due to improve of rhizomata cum radicibus growth 31 . Similar results were found by Sidhiq et al (2020) in E. purpurea plants grown in floating raft system for 21 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Soil calcium (Ca 2+ ) and magnesium (Mg 2+ ) were measured titrimetrically, K + was determined by flame photometry, sulfate (SO 4 2− ) by spectrophotometric and turbidimetric methods, NO 3 − and phosphate (PO 4 3− ) by colorimetry with an ultraviolet-visible (UV-Vis) spectrophotometer 11 . Available micronutrients (Cu, Fe, Mn, Mo, and Zn) and heavy metals (Cd, Ni, Pb) were extracted with a solution containing 0.005 mol L −1 diethylene triamine penta acetic acid (DTPA), 0.01 mol L −1 calcium chloride, and 0.1 mol L −1 (pH 7.3) triethanolamine (TEA), as well as, boron (B) concentration was determined based on hot water method 26,31 . The concentration of micronutrients were measured by Atomic Absorption Spectrophotometer (AAS) (Model Varian Spectra-220).…”
Section: Materials and Methods Experimental Backgroundmentioning
confidence: 99%